Some Comments on The Soviet Land and Water Reforms in Uzbekistan In the Early Twentieth Century and Its Consequences - YUNUSOVA, KHURSHIDA ERKINOVNA (The journal of contemporary issues in business and government, 2021)
The Bolshevik government, which came to power after the October coup, continuously politicized socio-economic life. In land and water relations, special attention was paid to the abolition of private property and the establishment of collective farms instead of small farms. These efforts became a complete barrier to economic development opportunities by limiting healthy market relations. The political events of 1917 in Turkestan devastated all sectors of the economy, especially the agricultural sector.